The Role of Interstitial Matrix and the Lymphatic System in Gastrointestinal Lipid and Lipoprotein Metabolism - Zhou, Anna; Qu, Jie; Liu, Min; Tso, Patrick (Frontiers in Physiology, 2020)
This review emphasizes the events that take place after the chylomicrons are secreted by the enterocytes through exocytosis. First, we will discuss the journey of how chylomicrons cross the basement membrane to enter the lamina propria. Then the chylomicrons have to travel across the lamina propria before they can enter the lacteals. To understand the factors affecting the trafficking of chylomicron particles across the lamina propria, it is important to understand the composition and properties of the lamina propria. With different degree of hydration, the pores of the lamina propria (sponge) changes. The greater the hydration, the greater the pore size and thus the easier the diffusion of the chylomicron particles across the lamina propria to enter the lacteals. The mechanism of the entry of lacteals is discussed in considerable details. We and others have demonstrated that intestinal fat absorption, but not the absorption of protein or carbohydrates, activates the intestinal mucosal mast cells to release many products including mucosal mast cell protease II in the rat. The activation of intestinal mucosal mast cells by fat absorption involves the process of chylomicron formation since the absorption of both medium and short chain fatty acids do not activate the mast cells. Fat absorption has been associated with increased intestinal permeability. We hypothesize that there is a link between fat absorption, activation of mucosal mast cells, and the leaky gut phenomenon (increased intestinal permeability). Microbiome may also be involved in this chain of events associated with fat absorption. This review is presented in sequence under the following headings: 1) Introduction; 2) Structure and properties of the gut epithelial basement membrane; 3) Composition and physical properties of the interstitial matrix of the lamina propria; 4) The movement of chylomicrons across the interstitial matrix of the lamina propria and importance of the hydration of the interstitial matrix of the lamina propria and the movement of chylomicrons; 5) Entry of the chylomicrons into the intestinal lacteals; 6) Activation of mucosal mast cells by fat absorption and the metabolic consequences; 7) Link between chylomicron transport, mucosal mast cell activation, leaky gut, and the microbiome.